Konsepsi dan Limitasi Toleransi dalam Merayakan Keberagaman dan Kebebasan Manusia - Futaqi, Sauqi (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper seeks to analyze the context of the emergence of the concept of tolerance. The examination of the context is to be expected to address the deadlock of the concept of tolerance among issues of diversity and freedom. In addition, tolerance also often has been at the dead lock when faced to intolerant actions that hide behind rights and differences. Therefore, the concept of tolerance also requires a study of the limitations of tolerance in responding to various issues of diversity and freedom. Tolerance and its limits will be the focus of the study in this paper. By tracking various sources of literature associated with later problems, it is hoped to clarify the building of the theory of tolerance